Conductivity of polymethylmethacrylate filled with carbon black or carbon fibres under oscillatory shear - Krückel, Johannes; Stary, Zdenek; Triebel, Christian; Schubert, Dirk W.; Münstedt, Helmut (Polymer, 2012)
The electrical conductivity of polymer composites containing conductive fillers is strongly influenced by the structure of the particle network. Therefore, the change of this network under deformation in the molten state is of great interest, in order to obtain materials with desirable electrical properties. In this work polymethylmethacrylate containing carbon black or carbon fibres was exposed to oscillatory shear deformations and the electrical conductivity of the materials was measured simultaneously. It was found that the particle networks in the composites filled with carbon fibres were more sensitive to deformation than those of the carbon black composites. The stability of the networks increased with growing amount of fillers. Furthermore, it could be shown that conductive and rheological networks behave completely different under shear deformations.
Keywords: Polymer composites; Rheology; Conductivity

Elasticity of polystyrene melts filled with silica nanoparticles: Influence of matrix polydispersity - Triebel, Christian; Kunzelmann, Peter; Schubert, Dirk W.; Münstedt, Helmut (Final Program and Book of Abstracts, 2011)

Influence of matrix polydispersity on the viscoelastic properties of polystyrene melts filled with nano silica - Triebel, Christian; Kunzelmann, Peter; Schubert, Dirk W.; Münstedt, Helmut (Book of Abstracts, 2012)

Investigations on the quality of dispersion of nanofillers in poly(methyl methacrylate) by creep-recovery experiments - Triebel, Christian; Kunzelmann, Peter; Katsikis, Nikolaos; Stara, Hana; Schubert, Dirk W. (Book of Abstracts, 2012)

Polyurethane/silver-nanocomposites with enhanced silver ion release using multifunctional invertible polyesters - Peukert, Wolfgang; Damm, Cornelia; Triebel, Christian; Vasylyev, Serhiy; Stara, Hana; Özpinar, Celal; Münstedt, Helmut; Hausmann, Sebastian (Journal of Materials Chemistry, 2011)
Nano-silver composites with a thermoplastic polyurethane as the matrix were prepared by two different routes. Using the so-called in situ preparation, silver nanoparticles were obtained by a thermal reduction of silver acetate during melt mixing. In addition, a more sophisticated ex situ preparation method was developed. Here, the silver nanoparticles are synthesized in an invertible polyester resulting in much smaller particle sizes. The particles obtained are surrounded by the polyester cage, which stabilizes them with respect to agglomeration. Hence, an incorporation of those particles into a polymer melt with common techniques like extrusion leads to an even distribution. This is due to the fact that the invertible polyester and the polymer matrix are entirely miscible which was proven with DSC measurements. The silver ion release of the composites prepared was measured with anodic stripping voltammetry. At a constant weight percentage of silver in the polymer, the composite with the ex situ silver nanoparticles exhibits a silver ion release which is about two orders of magnitude higher than the release from the composite with the in situ silver nanoparticles. This observation is explained by the higher specific surface area of the smaller particles and a higher coefficient of diffusion for silver ions. A concentration of only 0.07 wt% silver nanoparticles, prepared with the ex situ method, exhibits a high enough release of silver ions to achieve antimicrobial properties. © 2011 The Royal Society of Chemistry.
Keywords: nanoparticle; polymer; thermal; reduction; ex-situ